Characterisation of graphite nanoplatelets (GNP) prepared at scale by high-pressure homogenisation. Issue 21 (10th May 2019) - Guerra, Valentina; Wan, Chaoying; Degirmenci, Volkan; Sloan, Jeremy; Presvytis, Dimitris; Watson, Michael; McNally, Tony
Abstract : Graphite nanoplatelets (GNP) were prepared by a high-pressure homogenisation process (HPHP) via exfoliation of bulk graphite, yielding GNP in the form of square shaped platelets with lateral dimensions on the micrometre (μm) scale and thicknesses on the nanometre (nm) scale (<200 nm). Abstract : Graphite nanoplatelets (GNP) were prepared by a high-pressure homogenisation process (HPHP) via exfoliation of bulk graphite, yielding GNP in the form of square shaped platelets with lateral dimensions on the micrometre (μm) scale and thicknesses on the nanometre (nm) scale (<200 nm). The platelets have a polycrystalline structure with d 002 = 0.335 nm and L 002 = 2 nm, with a low crystalline defect concentration confirmed by weak D and D′ bands in the Raman spectra. The shift in the G band from 1587 cm −1 (graphene) to 1580 cm −1 (GNP) and the asymmetric G′ band combined with a decrease in I G′ / I G from 0.45 for the bulk graphite to 0.40 for the GNP confirmed a partially exfoliated structure. X-ray photoelectron spectroscopy (XPS) confirmed the presence of impurities on the GNP surface due to the surfactant used during the exfoliation process. Contact angle measurements (67° ± 2° (0 s), 64° ± 2° (10 s)) suggested the surface of the GNP was hydrophilic. The as produced GNP is a macro-porous material with sheet-like particles having non-uniform shape and size and a BET surface area of ca. 94 m 2 g −1 . The GNP is thermally stable under oxidative conditions up to 430 °C. The HPHP process is readily scalable and provides a cost effective route for the production of GNP.